2005
DOI: 10.1111/j.1365-2249.2005.02780.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus and neutrophil activation

Abstract: SummaryRespiratory syncytial virus infects almost all children by 2 years of age. Neutrophils are the predominant airway leucocytes in RSV bronchiolitis and they are activated in the presence of infection. However it is not clear whether RSV can directly signal to activate neutrophil cytotoxic function. To investigate this we have used a preparation of RSV washed using a new centrifugal diafiltration method to rapidly remove inflammatory molecules produced by the epithelial cells used to propagate the RSV stoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 22 publications
5
80
1
1
Order By: Relevance
“…Neutrophilic exocytosis is a major cause of epithelial damage and airway obstruction contributing to ventilation compromise during RSV disease in children (37,42). VEGF interaction with endothelium can regulate adhesion molecule expression and even enhance neutrophil emigration; however, in this case the reduced neutrophil recruitment was likely due to diminished virus replication as this is a significant regulator of neutrophil emigration in RSV disease (4,22,43).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophilic exocytosis is a major cause of epithelial damage and airway obstruction contributing to ventilation compromise during RSV disease in children (37,42). VEGF interaction with endothelium can regulate adhesion molecule expression and even enhance neutrophil emigration; however, in this case the reduced neutrophil recruitment was likely due to diminished virus replication as this is a significant regulator of neutrophil emigration in RSV disease (4,22,43).…”
Section: Discussionmentioning
confidence: 99%
“…In our experience the rapid onset of ciliostasis is frequently attributed to the presence of a toxin or to the nonphysiological nature of the carrier fluid; solutions with a low pH can cause rapid ciliostasis [18]. Another study reported that the addition of unwashed ultraviolet-irradiated RSV increased toxicity to HeLa cells, suggesting their viral preparation may have contained a toxic contaminant [13]. However, it is possible that the factors other than the presence of virus resulted in the rapid ciliostasis seen in the study by TRISTRAM et al [6].…”
Section: Basal Cell Cultures Infected With Rsv Increase Secretion Of mentioning
confidence: 99%
“…Stocks were harvested by disruption with glass beads for 1 min and the supernatant was centrifuged at 10006g for 5 min to remove cell debris. The filtrate was then purified by centrifugation through a polyethersulfone membrane with a pore size of 1000 kDa molecular weight cut-off (Vivaspin-20; Vivascience, Gloucester, UK), as previously described [13]. The virus fractions were collected and pooled in bronchial epithelial cell basal medium (BEBM; Lonza, Slough, UK), and aliquots containing about 0.5-1610 6 plaque-forming units (PFU)?mL -1 were stored at -80uC.…”
Section: Virus Strains and Growth Conditionsmentioning
confidence: 99%
“…The cause of FI-RSV vaccine-enhanced disease is not fully understood yet, but is assumed to be caused by multiple parameters including FI-RSV vaccine-induced Th2-biased immune responses (IL-4, IL-5, IL-13), neutrophils, and eosinophil infiltration in lungs after RSV infection. 33,34 The general features of FI-RSV vaccine-enhanced disease as represented by pulmonary histopathology in humans could be recapitulated in mice. However, detailed pathological features of RSV disease appear to be different in mice and humans.…”
mentioning
confidence: 99%